Trials and tribulations of market responses to climate change: Insight through the transformation of the Australian electricity market. Issue 4 (November 2019) - Dodd, Tracey; Nelson, Tim
We analyse the energy transition from coal to renewable. Our research contributes to the literature on transitions and grand challenges. Mitigating the effects of dangerous human-induced climate change requires Australia to adopt a 'carbon budget' of no more than 10 Gt between 2015 and 2050. To achieve this, the Australian electricity sector must reduce greenhouse gas emissions to at least net zero emissions by 2050. Australia's strategic response to climate change will have a significant influence on greenhouse gas emissions across Asia and the Pacific. The transition to renewables has proved difficult. The Liddell case study, involving closure of an ageing coal-fired power station, shows how the transition was impeded by institutional decisions. While firm-level actors recognised opportunities, regulators resisted the transition. Our research illustrates that transitions for grand challenges may require a relational stakeholder review, beyond the concept of short-term win–wins. JEL Classification:L02, D02, Q05